Solar Dollars: A Complementary Currency that Incentivizes Renewable Energy - Greco, Thomas H. (Frontiers in Built Environment, 2021)
Incentives are the key to addressing climate change and the various other aspects of the current multi-dimensional mega-crisis. This paper proposes the issuance of private community currency vouchers by electric utility companies based on their willingness and ability to provide their customers with energy derived from renewable sources. By monetizing the value of renewable energy in the form of a community currency Solar Dollars help to solve several critical problems at once: They incentivize a more rapid shift to renewable energy, help communities to become more resilient and self-determined, and enable the decentralization of economic and political power.